The influence of parents' oral health literacy and behavior on oral health of preschool children aged 3-6 years- evidence from China - Kan Wu; Wei yin; Xinhua Liang; Ling Zou; Zheng Yang (BMC, 2024)
Abstract Background Direct and indirect associations have been identified among health literacy, health behavior, and health status. Thus, we aimed to investigate the influence of oral health literacy and behaviors in parents on their children's oral health status. Moreover, we aimed to analyze the mentioned mediating effects through oral health behavior management. Methods Oral health information of 1,102 preschool children aged 3 to 6 years was collected from five primary schools in Jinjiang District, Chengdu City, Sichuan Province, China. The decay-missing-filled teeth (DMFT) index and soft scale plaque index (PI) were used by professional dentists aided by school teachers to assess caries and periodontal health among the children. Simultaneously, we conducted a questionnaire-based survey among the parents to determine their oral health literacy and health behavior and their children's oral health behavior. The probit model, instrumental variables, and mediation effect model were used to evaluate the association of parents' oral health literacy and behavior with their children's oral health status. Results The DFMT index was 1.58 among the children, with zero caries in 646 (58.6%) children. The PI was 0.68, with zero gum disease in 517 (46.9%). The univariate analysis suggested that the parents' health literacy and behavior were correlated with their children's oral health status (P < 0.01). Parents' oral health behavior significantly affected their children's oral health status. Simultaneously, a stronger correlation was observed upon using parents' health literacy as an instrumental variable to assess the endogeneity, indicating endogeneity problems. Parents' health-related behaviors exerted a mediating effect on children's oral health, with parents helping children brush their teeth demonstrating the strongest effect. Conclusion Parents' oral health-related behaviors can affect their children's oral health status. We recommend enhancing parents' oral health literacy to improve children's oral health status.